SURFACE ROUGHNESS AND CANDIDA ALBICANS BIOFILM FORMATION ON A RELINE RESIN AFTER LONG-TERM CHEMICAL DISINFECTION AND TOOTHBRUSHING - Izumida, Femanda E. [UNESP]; Jorge, Janaina Habib [UNESP]; Ribeiro, Roberta C. [UNESP]; Pavarina, Ana Claudia [UNESP]; Moffa, Eduardo B. [UNESP]; Giampaolo, Eunice T. [UNESP] (Elsevier B.V., 2014)
Statement of problem. Routine cleaning of a denture may increase the surface roughness of the material.Purpose. The purpose of this study was to investigate the effect of denture cleansers and time on the roughness and Candida albicans biofilm formation on a reline resin.Material and methods. Specimens of Tokuyama Rebase Fast II (20x 10x2 mm) were prepared and divided into 9 groups (n=15): Test groups were toothbrushed (30 cycles per day) in 1 of the following solutions: water, soap, or toothpaste. After toothbrushing, the specimens were immersed in solutions of water, sodium perborate, or chlorhexidine. These treatments were done once a day for 365 days. The surface roughness was evaluated at 0, 7, 15, 30, 90, 180, 270, and 365 days, and the C albicans biofilm formation was measured after 365 days. The roughness data were analyzed by 3-way repeated measures ANOVA and the Tukey test (alpha=.05), and the C albicans biofilm formation was analyzed by 2-way ANOVA.Results. Significant differences were found in the toothbrush and time interaction and in the toothbrush, immersion, and time interaction (P<.001). No significant differences were found between the toothbrush agent and chemical disinfection (P=.085) or between chemical disinfection and time interaction (P=.604). Brushing with dentifrice (PPb and PCh) showed a gradual decrease in surface roughness. The comparison among groups showed that PCh produced the lowest values of roughness. For C albicans biofilm formation, no significant differences were found among the experimental groups.Conclusions. The roughness values ranged from 0.31 to 0.69 mu m for all evaluated groups. For all groups, no significant differences were found in the quantification of C albicans.